2014
DOI: 10.2166/wh.2014.057
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial composition in a metropolitan drinking water distribution system utilizing different source waters

Abstract: We investigated the bacterial composition of water samples from two service areas within a drinking water distribution system (DWDS), each associated with a different primary source of water (groundwater, GW; surface water, SW) and different treatment process. Community analysis based on 16S rRNA gene clone libraries indicated that Actinobacteria (Mycobacterium spp.) and α-Proteobacteria represented nearly 43 and 38% of the total sequences, respectively. Sequences closely related to Legionella, Pseudomonas, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 33 publications
6
33
0
Order By: Relevance
“…Among 12 samples, the sample L contained the most phyla. The study showed that the microbial community of water originating from SW is more diverse than GW (Gomez-Alvarez et al 2015).Within the Proteobacteria phylum, a-Proteobacteria was the most dominant class in each water sample, followed by c-, b-, and d-Proteobacteria (Table S3), consistent with results from a previous study (Kwon et al 2011) in which a-Proteobacteria was more abundant than others. However, Huang et al (2014) reported that b-Proteobacteria was more abundant in drinking water, and Pinto et al (2012) showed that b-Proteobacteria (40%) was more abundant Figure 6.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Among 12 samples, the sample L contained the most phyla. The study showed that the microbial community of water originating from SW is more diverse than GW (Gomez-Alvarez et al 2015).Within the Proteobacteria phylum, a-Proteobacteria was the most dominant class in each water sample, followed by c-, b-, and d-Proteobacteria (Table S3), consistent with results from a previous study (Kwon et al 2011) in which a-Proteobacteria was more abundant than others. However, Huang et al (2014) reported that b-Proteobacteria was more abundant in drinking water, and Pinto et al (2012) showed that b-Proteobacteria (40%) was more abundant Figure 6.…”
Section: Discussionsupporting
confidence: 88%
“…The study showed that the microbial community of water originating from SW is more diverse than GW (Gomez‐Alvarez et al. ).Within the Proteobacteria phylum, α ‐Proteobacteria was the most dominant class in each water sample, followed by γ ‐, β ‐, and δ ‐Proteobacteria (Table S3), consistent with results from a previous study (Kwon et al. ) in which α ‐Proteobacteria was more abundant than others.…”
Section: Discussionmentioning
confidence: 99%
“…This means that the inclusion of a new biofilm's members depends on the selection process of the microbial community (or core) that develops the biofilm. Abiotic factors such as temperature, water quality, and aging time [47,52,53] had stronger influences on the active renewal of biofilm because they have a greater effect on the physicochemical and biological process in the environment.…”
Section: Microbial Community Analysesmentioning
confidence: 99%
“…An analysis of urban soils from the street green belts of the city of Chicago, USA, revealed that soils along a one‐way street showed higher Shannon and phylogenetic diversities than other soils, including those along a two‐way street, a feature that could be correlated with soil pH, moisture and texture (Wang et al ., ). We believe that the microorganisms living in the street, in street gutters and on pedestrian surfaces may present specific surface‐associated diversity, such as the ones identified on concrete (Domingo et al ., ; Li et al ., ; Gomez‐Alvarez et al ., ; Jiang et al ., ; Cayford et al ., ; Cowle et al ., ; Li et al ., ) or buildings and monuments (Ragon et al ., ; Chimienti et al ., ; Gaylarde et al ., ; Adamiak et al ., ; Dyda et al ., ).…”
Section: Introductionmentioning
confidence: 99%